Obviously strategy-proofness and generalized median voter schemes - Arribillaga, Roberto Pablo (2019)
The set of all strategy-proof and onto social choice functions on the domain of single-peaked preferences over a finite and linearly ordered set of alternatives coincides with the class of all generalized median voter schemes. Our objective in this paper is to characterize the subclass of generalized median voter schemes that, in addition of being strategy-proof, are also obviously strategy-proof. Our proof is constructive: for each obviously strategy-proof generalized median voter scheme we define an extensive game form that implements it in obviously dominant strategies.